STRATEGI MENINGKATKAN MUTU PARTISIPASI MASYARAKAT DI MI TAKHASUS DARUL ULUM NGALIYAN SEMARANG - Ardi Pramana; Nuriyatul Hidayah; Prayitno (Al-Mahabbah : Jurnal Manajemen Pendidikan Islam, 2025)
The role of community participation in Islamic educational institutions, particularly Madrasah Ibtidaiyah (MI), is increasingly recognized as essential for improving institutional quality and student outcomes. This study investigates the strategies implemented by MI Takhasus Darul Ulum Ngaliyan Semarang to enhance the quality of community involvement in school management. The aim is to explore how collaborative practices between the school and its surrounding community contribute to educational development. This qualitative research employs a case study approach supported by data from observations, interviews, and document analysis. The findings reveal that the madrasah has adopted inclusive strategies such as transparent communication, involvement in decision-making, utilization of local human resources, and open participation in both managerial and instructional activities. Community participation is manifested in both physical forms (e.g., infrastructure support, event committees) and non-physical forms (e.g., teaching, training, donations). These collaborative efforts have contributed to increased public trust, a 27% rise in student enrollment over two years, improved learning environments, and a strong sense of ownership among stakeholders. The study concludes that effective community engagement, when supported by visionary leadership and contextualized strategies, serves as a foundational pillar in building a resilient and sustainable educational ecosystem in Islamic schools. The model presented by MI Takhasus Darul Ulum offers practical insights for other Islamic educational institutions seeking to strengthen community-based governance